Automated Solid‐Phase Synthesis of Chondroitin Sulfate Glycosaminoglycans1. Issue 22 (15th April 2013) - Eller, Steffen; Collot, Mayeul; Yin, Jian; Hahm, Heung Sik; Seeberger, Peter H.
<x xml:space="preserve">Abstract</x> Glycosaminoglycans (GAGs) are important sulfated carbohydrates prevalent in the extracellular matrix. The synthesis of structurally defined GAGs requires laborious procedures, and incorporating defined sulfation patterns is challenging. The automated synthesis of defined sulfated chondroitin hexasaccharides on solid support has been achieved using a photolabile linker that is efficiently cleaved in a continuous‐flow photoreactor.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>